Temporal Delays Along the Neurosurgical Care Continuum for Traumatic Brain Injury Patients at a Tertiary Care Hospital in Kampala, Uganda. Issue 1 (26th February 2018) - Vaca, Silvia D; Kuo, Benjamin J; Nickenig Vissoci, Joao Ricardo; Staton, Catherine A; Xu, Linda W; Muhumuza, Michael; Ssenyonjo, Hussein; Mukasa, John; Kiryabwire, Joel; Rice, Henry E; Grant, Gerald A; Haglund, Michael M
Abstract: BACKGROUND: Significant care continuum delays between acute traumatic brain injury (TBI) and definitive surgery are associated with poor outcomes. Use of the "3 delays" model to evaluate TBI outcomes in low- and middle-income countries has not been performed. OBJECTIVE: To describe the care continuum, using the 3 delays framework, and its association with TBI patient outcomes in Kampala, Uganda. METHODS: Prospective data were collected for 563 TBI patients presenting to a tertiary hospital in Kampala from 1 June to 30 November 2016. Four time intervals were constructed along 5 time points: injury, hospital arrival, neurosurgical evaluation, computed tomography (CT) results, and definitive surgery. Time interval differences among mild, moderate, and severe TBI and their association with mortality were analyzed. RESULTS: Significant care continuum differences were observed for interval 3 (neurosurgical evaluation to CT result) and 4 (CT result to surgery) between severe TBI patients (7 h for interval 3 and 24 h for interval 4) and mild TBI patients (19 h for interval 3 and 96 h for interval 4). These postarrival delays were associated with mortality for mild ( P = .05) and moderate TBI ( P = .03) patients. Significant hospital arrival delays for moderate TBI patients were associated with mortality ( P = .04). CONCLUSION: Delays for mild and moderate TBI patients were associated with mortality, suggesting that quality improvement interventions could target current triage practices. Future research should aim to understand the contributors to delays along the care continuum, opportunities for more effective resource allocation, and the need to improve prehospital logistical referral systems.